Does cannabis use modify the effect of post-traumatic stress disorder on severe depression and suicidal ideation? Evidence from a population-based cross-sectional study of Canadians. (February 2020) - Lake, Stephanie; Kerr, Thomas; Buxton, Jane; Walsh, Zach; Marshall, Brandon DL; Wood, Evan; Milloy, M-J
Background: Post-traumatic stress disorder sharply increases the risk of depression and suicide. Individuals living with post-traumatic stress disorder frequently use cannabis to treat associated symptoms. We sought to investigate whether cannabis use modifies the association between post-traumatic stress disorder and experiencing a major depressive episode or suicidal ideation. Methods: We used data from the 2012 Canadian Community Health Survey-Mental Health, a nationally representative cross-sectional survey of non-institutionalized Canadians aged ⩾15 years. The relationship between post-traumatic stress disorder and each outcome was modelled using logistic regression with an interaction term for cannabis and post-traumatic stress disorder, controlling for demographic characteristics, mental health, and substance use comorbidities. The ratio of odds ratios and relative excess risk due to interaction was calculated to measure interaction on the multiplicative and additive scales, respectively. Results: Among 24, 089 eligible respondents, 420 (1.7%) reported a current clinical diagnosis of post-traumatic stress disorder. In total, 106 (28.2%) people with post-traumatic stress disorder reported past-year cannabis use, compared to 11.2% of those without post-traumatic stress disorder ( p < 0.001). In multivariable analyses, post-traumatic stress disorder was significantly associated with recent major depressive episode (adjusted odds ratio = 7.18, 95% confidence interval: 4.32–11.91) and suicidal ideation (adjusted odds ratio = 4.76, 95% confidence interval: 2.39–9.47) among cannabis non-users. post-traumatic stress disorder was not associated with either outcome among cannabis-using respondents (both p > 0.05). Conclusions: This study provides preliminary epidemiological evidence that cannabis use may contribute to reducing the association between post-traumatic stress disorder and severe depressive and suicidal states. There is an emerging need for high-quality experimental investigation of the efficacy of cannabis/cannabinoids for the treatment of post-traumatic stress disorder.